Authorship patterns and degree of collaboration of Sri Lankan scientific publications in Social sciences and Humanities – a picture from SCOPUS - Navaneethakrishnan, S. (University of Nebraska - Lincoln, 2014)
[The purpose of this study is to identify the authorship patterns and degree of collaboration of Sri Lanka in humanities and social science research with a total of 1795 records of publications authored by 3521 authors during the period 1960 – 2012 (inclusive) derived from SCOPUS database. The research method of this study was Bibliometric analytical method. Findings of the analysis revealed that the majority of the publications are contributed by multiple authors. Degree of collaboration was progressively increased over the study span. Remarkable collaborative contributors are from United States with 15.93%.]
Keywords: Bibliometrics; Sri Lanka; Social sciences; Authorship pattern